Early DNA methylation at the NGFI-A binding site of the NR3C1 1F promoter predicts cognitive functions at age five: Evidence from the Parents as Teachers intervention in the ZEPPELIN study - Elena Silvia Gardini; Alex Neuhauser; Simone Schaub; Isabelle Kalkusch; Patsawee Rodcharoen; Ulrike Ehlert; Andrea Lanfranchi; Gustavo Turecki; Peter Klaver (PLoS ONE, 2026)
Background The present study examines the link between DNA methylation at the nerve growth factor-induced protein A (NGFI-A) binding domain of the NR3C1 1F promoter and later cognitive functions in children from families living in disadvantaged psychosocial conditions. Methods Participants were 132 children who took part in a Swiss Parents as Teachers (PAT) randomized controlled trial (72 in the intervention group, 60 in the control group). DNA methylation was quantified from saliva samples collected at age three using sodium bisulfite next-generation sequencing (NGS). Cognitive functions were assessed at age five using the SON-R 2.5–7 Intelligence Test. Results (a) DNA methylation at age three was associated with lower IQ at age five through increased concentration problems (indirect effect = −0.083, p = .012); (b) parental disagreement was associated with concentration difficulties through DNA methylation (indirect effect = 0.064, p = .023); and (c) participation in the three-year PAT program was associated with lower methylation levels (β = −0.375, p = .041). The serial pathway from parental disagreement to IQ via methylation and concentration was not significant. Conclusions These findings provide preliminary evidence for an association between early DNA methylation at the NGFI-A binding site of the NR3C1 1F promoter and later cognitive functions in children and highlight the potential role of early life stressors and the PAT intervention in shaping these associations. However, given the exploratory nature of this study, replication in larger independent samples is warranted.